Activity Test of bitter melon Leaf Infusion (Momordica charantia) as an anthelmintic toward Ascaridia galli worms in vitro - Andi Muhammad Taufan; Adriyani Ris; Magfira Satya Apada; Jamaluddin, Abdul Wahid (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2023)
Ascaridia galli is a gastrointestinal parasite in poultry which can cause weight loss, slow growth and affect egg production. Chickens that are infected can cause damage to the integrity of the intestinal villi to severe inflammation of the intestinal mucosa. Bitter melon leaf (Momordica charantia) is known to have an anthelmintic effect which can be used as an alternative in the treatment of worms disease. The purpose of the research is to determine activity of bitter melon leaf infusion toward Ascaridia galli conducted in vitro. In the research, it uses 72 Ascaridia galli that divided into 4 groups consisting of positive control group (Levamid), negative control group (Aquadest), and 2 treatment group with 10%, and 20% bitter melon leaf infusion concentration, respectively. Each group replicated three times. The worms were immersed in the test solution and observations were performed every 15 minutes and counted the number of worms that died. The results showed that pare leaf infusion with concentrations of 10% and 20% had an anthelmintic effect but was no better than Levamid as a positive control.